The Genre of Autobiography During Medieval Period: Exploring the Autobiographical Genre in Medieval India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This article attempts to indicate that the genre ofautobiography was produced not merely in western tradition but it also aboundedin Medieval India. The noteworthy autobiographer was Babur who adhered to thedesign and truth as enunciated by Roy Pascal in his well-known authoritativebook “Design and Truth in Autobiography”.